Clinicopathological Study of Bladder Outflow Obstruction:Study of 300 Cases - Rakib, Md Abdur; Islam, Md Shahidul; Waheed, SM Shameem; Sajal, Hafizur Rashid (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.55-62